Temperature influences glyphosate efficacy on glyphosate-resistant and -susceptible goosegrass (Eleusine indica) - Guo, Wenlei; Zhang, Chun; Wang, Siwei; Zhang, Taijie; Tian, Xingshan (Frontiers in Plant Science, 2023)
Glyphosate has been widely used to control Eleusine indica and other weeds in South China for many years. Among the most troublesome weeds in South China, E. indica can remain alive all year round. However, the influence of temperature on glyphosate efficacy on E. indica, especially under days with fluctuating temperature, is unknown. This study evaluated the influence of two temperature regimes on glyphosate efficacy on glyphosate-resistant (R) and -susceptible (S) E. indica biotypes. Plants of the R and S biotypes were cultivated under two temperature regimes (high: 30 ºC/20 ºC day/night; low: 20 ºC/15 ºC day/night). Dose-response experiments showed improved efficacy of glyphosate at the low temperature compared with that at the high temperature for both biotypes. Based on the LD50 values, the R biotype was 8.9 times more resistant to glyphosate than the S biotype at the high temperature; however, the resistance index (R/S) decreased to 3.1 at the low temperature. At 4 days after glyphosate application, shikimic acid accumulation was greater at the low temperature than at the high temperature in plants of both biotypes, and the increase was higher in plants of the R biotype than in the S biotype. At a sublethal glyphosate dose (R: 400 g ai ha−1; S: 200 g ai ha−1), plants grown at the low temperature showed a strong decrease in leaf chlorophyll content and Fv/Fm value compared with those of plants grown at the high temperature and the untreated control. At 3 days after treatment, glyphosate absorption was similar between biotypes at the high temperature, but absorption decreased to 64.9% and 53.1% at the low temperature for the R and S biotypes, respectively. For both biotypes, glyphosate translocation from the leaf to the remainder of the plant was reduced at the low temperature compared with that at the high temperature. No differences in glyphosate translocation were observed between biotypes within each temperature regime. This is the first report on the effect of temperature on glyphosate efficacy on E. indica, and provides important insights for glyphosate application and resistance management.